Effect of inspiratory muscle training in children with asthma: a systematic review and meta-analysis of randomized controlled trials - Xiang, Yuping; Luo, Tianhui; Chen, Xinyang; Zhang, Huanhuan; Zeng, Ling (Frontiers in Pediatrics, 2024)
Asthma is a common chronic respiratory disease in children. Alongside pharmacological interventions, inspiratory muscle training (IMT) emerges as a complementary therapeutic approach for asthma management. However, the extent of its efficacy in pediatric populations remains uncertain when compared to its benefits in adults. This systematic review aims to evaluate the effectiveness of IMT with threshold loading in children with asthma.: Randomized controlled trials (RCTs) evaluating the efficacy of inspiratory muscle training in pediatric asthma patients were identified through June 2023 across various literature databases, including PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAL), Web of Science, China Knowledge Resource Integrated Database (CNKI), Wei Pu Database, Wan Fang Database, and Chinese Biomedical Database (CBM). These trials compared inspiratory muscle training against sham inspiratory muscle training and conventional care.Eligible studies were assessed in terms of risk of bias and quality of evidence. Where feasible, data were pooled and subjected to meta-analysis, with results reported as mean differences (MDs) and 95% confidence intervals (CIs).Results: Six trials involving 333 patients were included in the analysis. IMT demonstrated significant improvements in maximum inspiratory pressure (MIP) (MD 25.36, P=0.03), maximum expiratory pressure (MEP) (MD 14.72,, P=0.006), forced vital capacity in percent predicted values [FVC(% pred)] (MD 3.90, 95%CI 1.86-5.93, P=0.0002), forced expiratory volume in the first second in percent predicted values [FEV1(% pred)] (MD 4.96, 95%CI 2.60-7.32, P<0.0001), ratio of forced expiratory volume in 1 sec to forced vital capacity (FEV1/FVC) (MD 4.94, 95%CI 2.66-7.21, P<0.0001), and asthma control test (ACT) (MD=1.86, 95% CI: 0.96-2.75, P<0.0001). Conclusions: Findings from randomized controlled trials indicate that inspiratory muscle training enhances respiratory muscle strength and pulmonary function in pediatric asthma patients.